Caregivers’ Compliance with COVID-19 Guidelines: A Study of Caregivers of Children with Intellectual Disability in Clinical Support and Therapeutic Management Home/School, Lagos, Nigeria - Ataben, Michael Okaba; Akpan, Victor Bassey; Manuel, Mojisola Nkechi; Enyi, Mary Ogban; Okpechi, Philip Abane; Ogban, Ogban Nkanu; Inah, Roland Afen; Inah, Emmanuel Mkpe; Obogo, Godwin Obogo; Udie, Lazarus Ishifundi; Eke, Vitalis Ugochukwu; Okoi, Ikpi Inyang; et al. (Journal of Intellectual Disability - Diagnosis and Treatment, 2026)
The COVID-19 pandemic presented serious challenges to special education systems, particularly for caregivers responsible for persons with Intellectual Disabilities (ID). Because of the low intellectual functioning, most individuals with ID lack the capacity to follow basic rules that can enhance their well-being; hence, they depend on caregivers for their everyday living. This study examined how caregivers’ attitudes and hazard incentives influenced their adherence to COVID-19 safety protocols in Childcare and Treatment Home/School Home/School, Akoka, Lagos, Nigeria. 159 caregivers participated in the study, employing a correlational survey approach. Data were collected using a researcher-designed instrument titled “Caregivers’ Attitude, Hazard Incentive, and COVID-19 Precautionary Compliance Questionnaire” (CAHICPCQ). The collected data were analysed using simple linear regression and multiple linear regression with dummy-coded hazard incentive variables. Results revealed that caregivers’ attitude significantly predict compliance with COVID-19 precautionary measures, F(1,157) = 48.99, R = .48, R² = .24, β = .49, p < .001. Hazard incentives also significantly influenced compliance at the model level, F(7,151) = 2.84, R² = .116, adjusted R² = .075, p = .008; however, among the individual incentive variables, only personal sanitiser availability was a significant positive predictor (B = 6.60, β = .177, p = .027). These findings emphasize the necessity of attitudinal training and institutional incentives to improve caregivers’ compliance, especially during public health emergencies. The study suggests that special education stakeholders should prioritize behavioural support programs and structured hazard incentive systems to protect caregivers and children with ID.